Intelligent Egg Incubator - Azahar, Kaiyisah Baiduri; Sekudan, Ericka Ensimau; Azhar, Ahmad Mirza (International Journal of Recent Technology and Applied Science (IJORTAS), 2020)
This research presents the design and development of a chicken egg incubator. The aim is to design and construct an “Intelligent Egg Incubator” that can hatch chicken eggs automatically. In the design, author used a temperature control system that controls the temperature of the incubator. This system consists of a temperature sensor, heating and cooling elements and a controller. If the temperature of the incubator exceeds a certain value, the cooling unit will operate to reduce the temperature while if the temperature goes below another threshold value, the heating element will start to operate to increase the temperature. Furthermore, author used a motion sensor to detect the movements of the eggs. If there is a movement inside the incubator, the owner of the incubator will get the notification about the conditions of the eggs